2007
DOI: 10.1007/s10517-007-0323-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of cardioprotective effects of uridine-5′-monophosphate and uridine-5′-triphosphate during the early periods of acute myocardial ischemia

Abstract: In experiments on rats, uridine-5'-monophosphate and uridine-5'-triphosphate reduced the intensity of anaerobic glycolysis and preserved glycogen stores and creatine phosphate balance during the first 60 min after occlusion of the left coronary artery. However, the energy-protective effect of uridine-5'-triphosphate developed 15 min later than the effect of uridine-5'-monophosphate. Uridine-5'-monophosphate, but not uridine-5'-triphosphate, reduced T wave amplitude on ECG and decreased the volume of ischemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recent data revealed that a higher level of plasma uridine reduces the tendency for atrial fibrillation and can be associated with a decreased atherosclerosis risk [48,49]. Our previous studies indicated that under ischemia and reperfusion conditions, uridine supplementation prevents myocardial redox dyshomeostasis and heart rhythm disorders [29,30]. A growing body of evidence suggests that uridine can induce tissue recovery and decrease pro-inflammatory cytokine levels in various models of cardiac injury and cell pathologies [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent data revealed that a higher level of plasma uridine reduces the tendency for atrial fibrillation and can be associated with a decreased atherosclerosis risk [48,49]. Our previous studies indicated that under ischemia and reperfusion conditions, uridine supplementation prevents myocardial redox dyshomeostasis and heart rhythm disorders [29,30]. A growing body of evidence suggests that uridine can induce tissue recovery and decrease pro-inflammatory cytokine levels in various models of cardiac injury and cell pathologies [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Uridine treatment can significantly decrease the levels of oxidative stress and inflammation in in vitro and in vivo models [33,51]. The positive effects of uridine against myocardial oxidative stress and inflammation may be associated with the activation of the mitoK ATP channel and normalization of the activity of antioxidant defense systems [29,30,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations